Development of computer integrated manufacturing (CIM) frameworks at UMP FKM laboratory - Dahlan, Hishahmuddin (2007)
Computer Integrated Manufacturing (CIM) system is known as a system that integrate all the data and information from business, manufacturing, management information until a product distribution into one system. CIM system will offer better factory control, improved product quality and product flexibility. Nevertheless, it is still new at FKM Laboratory at UMP. Even though currently FKM still do not produce anything for market sell but is good to have such as this system for future use. So that,every details and data about production at FKM could be monitored in one system. Before manage all the information needed to develop CIM system, every company must define and determine the most important element in CIM system based on their facilities and availability. The objective of this project is to develop the framework for CIM system in FKM Laboratory. The framework will guide in the process of development CIM system for FKM Laboratory for the future use This study also will define and determine the most important element in CIM based on FKM Laboratory. For the beginning, data and information from the making of mold for bottle plastic have been taken and used, which is as a foundation to develop CIM system. By utilizing this project, hopefully it will be as guideline for Faculty to implement the CIM system to FKM Lab furthermore to all laboratories in UMP.